Religion and Secularity Transformations and Transfers of Religious Discourses in Europe and Asia - Eggert, Marion; Hölscher, Lucian (Dynamics in the History of Religions, 2013)
Religion and Secularity assembles studies on the concept of "secularity" in various cultures, thereby tracing the entangled history of the modern re-configuration of the religious field across the Eurasion continent.; Readership: Academics interested in religious history, conceptual history, world history of (early) modern times, and regional specialists in European, Near Eastern, South Asian and East Asian Studies.